Direct healthcare costs for people with cerebral palsy in the Brazilian unified health system between 2015 and 2019 - Freire, Emilie Batista (2025)
Background: Estimate the costs of inpatient and outpatient care for people with Cerebral Palsy (CP) in Brazil. Research design and methods: Health records of people with CP in the Hospital and Outpatient Information Systems of Brazil between 2015 and 2019 were analyzed. Variables analyzed were gender, age, ICD, Intensive Care Unit (ICU) use, total cost, and ICU cost. Costs were adjusted for inflation and converted to dollars. Linear regression analysis was performed to investigate the association between social and clinical variables and direct costs. Results: A total direct cost of approximately $166 million to the National Health System was identified, with $7.08 million/year and $26.1 million/year of inpatient and outpatient costs, respectively. The healthcare was primarily for children up to 14 years of age. The ICD ‘spastic quadriplegic CP’ received the most attendance. Rehabilitation was responsible for 75% of the outpatient care, with physiotherapy standing out. Increased age, use of ICU, and the types of CP are related to increased cost. Conclusions: Healthcare for people with CP produced expressive costs for the Brazilian public health system, mainly with outpatient procedures and rehabilitation, with children being the most attended. Estimating these costs assist in better resource allocation for more effective healthcare provision.